PENGARUH MEDIA AUDIO VISUAL TERHADAP KECERDASAN LINGUISTIK SISWA KELAS I SDN MARGOREJO I SURABAYA PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Sukowati, Nur; Sulistyawati, Ida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is the low literacy ability of students, which is still at the minimum competency level (insufficient literacy). The researcher aims to determine the impact of using audiovisual media in enhancing students' linguistic intelligence as an alternative literacy tool besides books. This study was conducted to examine the effects of audiovisual media on the development of students' linguistic intelligence. A quantitative method was applied using a quasi-experimental design, with a posttest-only control design framework. Data collection techniques involved posttest assessments and observations. The data analysis methods used in this research included normality tests, homogeneity tests, and the Mann-Whitney test. The findings of this study were obtained from the